Psychoanalysis and the paranormal : lands of darkness - Totton, Nick (Karnac, 2003)
'The space of the paranormal can indeed be frightening. But psychoanalysis specializes in entering and tolerating frightening spaces. Why should this one be an exception?'-Nick Totton from the Foreword.